Translocator protein PET imaging in temporal lobe epilepsy: A reliable test-retest study using asymmetry index - Mahmud, Mohammad; Wade, Charles; Jawad, Sarah; Hadi, Zaeem; Otoul, Christian; Kaminski, Rafal M.; Muglia, Pierandrea; Kadiu, Irena; Rabiner, Eugenii; Maguire, Paul; Owen, David R.; Johnson, Michael R. (Frontiers in Neuroimaging, 2023)
Abstract Objective Translocator-protein (TSPO) targeting positron emission tomography (PET) imaging radioligands have potential utility in epilepsy to assess the efficacy of novel therapeutics for targeting neuroinflammation. However, previous studies in healthy volunteers have indicated limited test-retest reliability of TSPO ligands. Here we examine test retest measures using TSPO PET imaging in subjects with epilepsy and healthy controls, to explore whether this biomarker can be used an endpoint in clinical trials for epilepsy. Methods Five subjects with epilepsy and confirmed mesial temporal lobe sclerosis (mean age 36 years, 3 male) were scanned twice – on average 8 weeks apart – using a second generation TSPO targeting radioligand, [11C]PBR28. We evaluated the test-retest reliability of the volume of distribution and derived hemispheric asymmetry index of [11C]PBR28 binding in these subjects and compared the results with 8 (mean age 45, 6 male) previously studied healthy volunteers. Results The mean (± SD) of the volume of distribution (VT), of all subjects, in patients living with epilepsy for both test and retest scans on all regions of interest is 4.49 ± 1.54, versus 5.89 ±1.23 in healthy volunteers. The bias between test and retest in asymmetry index as % was small (-1.5%) and reliability is demonstrated here with Bland-Altman Plots (test mean 1.062, retest mean 2.56). In subjects with epilepsy, VT of [11C]PBR28 is higher in the (ipsilateral) hippocampal region where sclerosis is present than in the contralateral region. Conclusion When using TSPO PET in epilepsy patients with hippocampal sclerosis, inter-hemispheric asymmetry index in the hippocampus is a measure with good test-retest reliability. We provide estimates of test-retest variability that may be useful for estimating power where group change in VT represents the clinic outcome.